Correlation Compliance with the Implementation of Standard Operational Procedures Wound Treatment, Bundles Surgical Site Infection and Blood Sugar Levels with the Incident of Operative Site Infection in Sectio Ceasarea Patients - Slamet Djoko Sunarko; Yuly Peristiowati; Prima Dewi Kusumawati (Universitas STRADA Indonesia, 2024)
Non-compliance with wound care SOPs can trigger surgical site infections that result in increased morbidity and mortality, as well as increased length of care. The purpose of this study was to determine the relationship between compliance with the implementation of wound care SOPs, surgical site infection bundles, and blood sugar levels with the incidence of surgical site infections. Correlation research with a cross-sectional approach design. The independent variables of compliance with wound care SOPs, KGD, and the implementation of SSI bundles used observation.